Food Availability, Thermal Quality, and Habitat Selection in Yarrow’s Spiny Lizards (Sceloporus Jarrovii) - Patterson, Lucy (Université d'Ottawa / University of Ottawa, 2018)
Elucidating the factors that drive variation in the abundance and distribution of organisms is central to ecology. Variables that explain the spatial variation in the abundance of organisms primarily include environmental (e.g., temperature and precipitation) and biotic factors (e.g., competition, predation, and parasitism). An important mechanism influencing the spatial distribution of organisms, at least at small spatial scales, is habitat selection. Traditionally, habitat selection theory has assumed that animals select habitat based on their ability to acquire depletable resources within that habitat, especially food. Ectotherms, however, may instead select habitat based on their ability to process food within the habitat, given the strong dependence of body temperature (and performance) on environmental temperature in this group. The major objective of my thesis was to determine whether energy gain, habitat selection, and population density were driven primarily by food availability or by temperature in ectotherms. I used Sceloporus jarrovii lizards as a study species because these lizards occur at high densities and in similar habitat across a broad altitudinal range. In Chapter 1, I tested the prediction, central to the thermal coadaptation hypothesis, that juvenile lizards prefer body temperatures that maximize their net energy gain. I also tested whether lizards shifted their preferred body temperatures to correspond to the optimal temperature for different energetic states, as per Huey’s (1982) energetics model. In Chapter 2, I determined whether the home range size and density of lizards shifted in response to manipulations of food availability and/or thermal quality within a site. In Chapters 3 and 4, I determined whether mean body condition, individual growth rate, and population density were driven by food availability or thermal quality. In Chapter 3, I visited 32 study sites over a 1,550 m altitudinal range within a year; whereas in Chapter 4, I food-supplemented five out of 10 study sites where I performed mark-recapture over a period of three years. Overall, my thesis demonstrates that both food availability and thermal quality of the habitat drive energy gain, habitat selection, and population density. Juvenile S. jarrovii preferred body temperatures that maximized net energy gain, regardless of energetic state. Although they did not shift their preferred body temperature range depending on energetic state, the difference in the optimal temperature for net energy gain between states (0.4°C), may have been too small to warrant a change in behaviour. Within a site, S. jarrovii increased their home range size and occurred at higher densities as natural food availability increased, and decreased their home range size and occurred at lower densities as the thermal quality under the rocks increased. This suggests that S. jarrovii respond to food availability and thermal quality at different scales, selecting territories based on thermal quality and home ranges based on food availability. Over 32 sites, the abundance of S. jarrovii increased with food availability, whereas the mean body condition increased and the rate at which lizards attained their maximum body size decreased with elevation (at lower thermal quality). In the three-year study, mean body condition and individual growth rate decreased and population density increased with thermal quality, but the strength of the relationship depended on natural food availability. Overall, both food availability and thermal quality of the habitat drive energy gain, habitat selection, and population density; however, thermal quality is often the stronger driver. Thus, improvements to habitat selection models should incorporate habitat thermal quality to improve predictions on how ectotherms distribute themselves on a landscape.
Keywords: Habitat selection; Thermal ecology; Ectotherm; Reptile; Population density; Body condition; Growth rate; Home range